The androgen receptor cistrome is extensively reprogrammed in human prostate tumorigenesis - Pomerantz, Mark M. (Nat Genet, 2015)
Master transcription factors interact with DNA to establish cell-type identity and to regulate gene expression in mammalian cells(1,2). The genome-wide map of these transcription factor binding sites has been termed the cistrome(3). Here we show that the androgen receptor (AR) cistrome undergoes extensive reprogramming during prostate epithelial transformation in man. Using human prostate tissue, we observed a core set of AR binding sites that are consistently reprogrammed in tumors. FOXA1 and HOXB13, co-localized with the reprogrammed AR sites in human tumor tissue. Introduction of FOXA1 and HOXB13 into an immortalized prostate cell line reprogrammed the AR cistrome to resemble that of a prostate tumor, functionally linking these specific factors to AR reprogramming. These findings offer mechanistic insights into a key set of events that drive normal prostate epithelium towards transformation and establish the centrality of epigenetic reprogramming in human prostate tumorigenesis.